Understanding the Education Philosophy and Its Implications - Lamichhane, Chandra Dip (NCC Journal, 2018)
Education is the process of facilitating learning, or the acquisition of knowledge, skills, values, beliefs, and habits. Education is the development of all those capabilities in which the individual which is enable him to control his environment and fulfillment his possibilities. It is a process of acquiring new habits, knowledge & skill which together enables learners to do something that he/she could not do before. It is a mental activity by means of which skills, attitude, appreciation and ideas are acquired, resulting in modification of behaviors. The purpose of this article is to discussabout the philosophy, importance and implications of education processin our contemporary environment as well as the world. How the people acquire knowledge, ideas, and skills and utilize to those knowledge and ideas for the development and prosperity of humankind as well as the development of nation and the entire world is the main objective of this article. NCC Journal Vol. 3, No. 1, 2018, Page: 24-29